(untitled) (Current Horticulture, 2024)
Dolichos bean is a perennial herbaceous plant often grown as an annual mainly grown for its young pod and green immature seeds for vegetable purpose. Dolichos bean can grown in different agro climatic conditions due to its wide adaptability therefore, it is necessary to select variety having desired pod quality with high-yielding potential. It is however, desirable to know the degree to which different component characters are correlated (Sharma et al. 2014). The study was, therefore undertaken to determine correlation coefficients both at genotypic and phenotypic levels and the genotypic and phenotypic correlations were computed by using the formula given by Panse and Sukhatme (1967).